ON PARTICLE WAVES SOLUTIONS OF THE EQUATION OF ETHER WAVES - Zareski, David (JOURNAL OF ADVANCES IN PHYSICS, 2015)
In previous publications, we demonstrated that the monochromatic waves ξ associated to particles, (including photons), submitted to forces, (gravitational regarding the photons), are the solutions of the ether elastic wave equation for sufficiently large pulsation ω. In these publications we did not considered the fact that it may exist waves ξ that are the solutions of this wave equation even for small values of ω, like for example waves associated to the free photons. In the present paper, we show cases where waves ξ associated to particles submitted to forces are solutions of this ether wave equation for any values of ω, i.e., even for its small values.